Selective inhibitory effects of HYIpro‐3‐1 on CYP1A2 in human liver microsomes. (2nd February 2021) - Kim, Younah; Kim, Ju‐Hyun; Lee, Taeho; Bae, Jong‐Sup; Jeong, Tae Cheon; Lee, Eung Seok; Lee, Sangkyu
Abstract: CYP1A2 is one of the main Cytochrome P450 enzymes in the human liver associated with the metabolism of several xenobiotics. CYP1A2 is especially involved in the metabolic activation of different procarcinogens. Therefore, the development of cancer may be inhibited by inhibiting CYP1A2 activity. Here, the inhibitory effect of HYIpro‐3‐1 and its derivatives on CYP1A2 activity in human liver microsomes (HLM) was studied through LC‐MS/MS using a cocktail assay. Among the four compounds, HYIpro‐3‐1 showed the most selective and strongest inhibitory effect on CYP1A2 at IC50 values of 0.1 µM in HLMs and inhibition was confirmed using purified human CYP1A2. It was determined that inhibition is reversible because the inhibitory effect of HYIpro‐3‐1 is not dependent on preincubation time. HYIpro‐3‐1 showed a typical pattern of competitive inhibition for CYP1A2‐catalyzed phenacetin O ‐deethylation, based on the Lineweaver‐Burk plot, with a Ki value of 0.05 μM in HLMs; the secondary plot also showed a linear pattern. In our study, HYIpro‐3‐1 was proposed as a novel inhibitor with the capacity to selectively inhibit CYP1A activity in HLMs.